Integrating corporate social responsibilities in business models that raising the living standards of the poor: Integracja CSR w modelach biznesowych umożliwiająca wzrost standardów życia - Kurovs, Jevgenijs (Management and Administration Journal, 2021)
What is a business model? Even though there are numerous definitions available in the literature, none of them provide a precise explanation of business model concept. The reason for this phenomenon is explained by Amit, Zott and Massa (2010) as follows, “business model is often studied without explicitly defining the concept. Of the 103 business model publications reviews 37% do not define the concept at all, taking its meaning more or less for granted. 44% explicitly define the concept of business model, e.g. enumerating its main components. The remaining publications (19%) define the concept. Moreover, existing definitions only partially overlap, giving rise to a multitude of possible interpretations…” (p.6). Our research paper examines the business model terminology through four main lenses. First we focus on the differences in constructs of business model and their definition as well as their place and role they play to in competitive strategy to outperform competitors. Second, we provide a theoretical foundation for the business model using the corporate social responsibilities (CSR) which can be embedded as important element of customer value proposition (CVP) or even as a driver that shape company ecosystem. Third, we explore how business models can be structured and executed to generate the necessary profits for companies while at the same time integrating and serving the poorest and their unique needs. Fourth, we outline an implication for further research based on our analysis and findings.